Laparoscopic repair for perforated peptic ulcer disease (Review) (2013)
ABSTRACT: BackgroundPerforated peptic ulcer is a common abdominal disease that is treated by surgery. The development of laparoscopic surgery has changedthe way to treat such abdominal surgical emergencies. The results of some clinical trials suggest that laparoscopic surgery could be abetter strategy than open surgery in the correction of perforated peptic ulcer but the evidence is not strongly in favour for or against thisintervention.ObjectivesTo measure the eGect of laparoscopic surgical treatment versus open surgical treatment in patients with a diagnosis of perforated pepticulcer in relation to abdominal septic complications, surgical wound infection, extra-abdominal complications, hospital length of stay anddirect costs.Search methodsWe searched the Cochrane Central Register of Controlled Trials (CENTRAL) on The Cochrane Library (2004, Issue 2), PubMed/MEDLINE(1966 to July 2004), EMBASE (1985 to November 2004) and LILACS (1988 to November 2004) as well as the reference lists of relevantarticles. Searches in all databases were updated in December 2009 and January 2012. We did not confine our search to English languagepublications.Selection criteriaRandomized clinical trials comparing laparoscopic surgery versus open surgery for the repair of perforated peptic ulcer using anymechanical method of closure (suture, omental patch or fibrin sealant).Data collection and analysisPrimary outcome measures included proportion of septic and other abdominal complications (surgical site infection, suture leakage, intraabdominal abscess, postoperative ileus) and extra-abdominal complications (pulmonary). Secondary outcomes included mortality, timeto return to normal diet, time of nasogastric aspiration, hospital length-of-stay and costs. Outcomes were summarized by reporting oddsratios (ORs) and 95% confidence intervals (CIs), using the fixed-eGect model.Main resultsWe included three randomized clinical trials of acceptable quality. We found no statistically significant diGerences between laparoscopicand open surgery in the proportion of abdominal septic complications (OR 0.66; 95% CI 0.30 to 1.47), pulmonary complications (OR0.52; 95% CI 0.08 to 3.55) or number of septic abdominal complications (OR 0.60; 95% CI 0.32 to 1.15). Heterogeneity was significant forpulmonary complications and operating time.